2020
DOI: 10.1186/s12943-020-01217-2
|View full text |Cite
|
Sign up to set email alerts
|

LINC00173.v1 promotes angiogenesis and progression of lung squamous cell carcinoma by sponging miR-511-5p to regulate VEGFA expression

Abstract: Background Anti-angiogenic therapy represents a promising strategy for non-small-cell lung cancer (NSCLC) but its application in lung squamous cell carcinoma (SQC) is limited due to the high-risk adverse effects. Accumulating evidence indicates that long noncoding RNAs (lncRNAs) mediate in tumor progression by participating in the regulation of VEGF in NSCLC, which might guide the development of new antiangiogenic strategies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 49 publications
1
105
0
1
Order By: Relevance
“…VEGFA (Vascular endothelial growth factor-A) is a primary factor driving expansion of the tumor vascular bed [25]. VEGFA is involved in the regulation of various tumor angiogenesis (such as lung squamous cell carcinoma [26], ovarian cancer [27], etc.). MMP2 and VEGFA are both recognized as the molecular biomarkers of tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…VEGFA (Vascular endothelial growth factor-A) is a primary factor driving expansion of the tumor vascular bed [25]. VEGFA is involved in the regulation of various tumor angiogenesis (such as lung squamous cell carcinoma [26], ovarian cancer [27], etc.). MMP2 and VEGFA are both recognized as the molecular biomarkers of tumor angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) are a type of RNA with lengths exceeding 200 nucleotides that do not encode proteins 11 . LncRNAs have attracted increasing attention as cancer biomarkers for early screening, diagnosis, prognosis and response to drug treatment 12‐14 . Although several lncRNAs including lncRNA ODRUL, 11,15 SNHG15, 16 SNHG16, 17 SNHG4 18 and AFAP1‐AS 19 have been confirmed to be highly correlated with OS, no widely applicable therapeutic targets have not been identified thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Some lncRNAs can serve as competitive endogenous RNAs (ceRNAs) of microRNA (miRNA/miR) to modulate the downregulation of miRNA targets (11). The functions of lncRNAs in cancer and several other diseases have been investigated (12)(13)(14)(15). For instance, Chen et al (12) reported that LINC00173.v1 upregulated the expression of VEGFA via sponging miR-511-5p to promote the proliferation and migration of vascular endothelial cells.…”
Section: Comprehensive Evaluation Of Differential Long Non-coding Rnamentioning
confidence: 99%
“…The functions of lncRNAs in cancer and several other diseases have been investigated (12)(13)(14)(15). For instance, Chen et al (12) reported that LINC00173.v1 upregulated the expression of VEGFA via sponging miR-511-5p to promote the proliferation and migration of vascular endothelial cells. Wang et al (13) also revealed that CARL lncRNA inhibited mitochondrial fission and apoptosis by upregulating prohibitin 2 expression via decreasing the expression of miR-539.…”
Section: Comprehensive Evaluation Of Differential Long Non-coding Rnamentioning
confidence: 99%